Playful virtual violence : an ethnography of emotional practices in video games - Bareither, Christoph (Cambridge elements. Elements in histories of emotions and the senses., 2020)
Violence in video games has been a controversial object of public discourse for several decades. The question of what kind of emotional experiences players enact when playing with representations of physical violence in games has been largely ignored however. Building upon an extensive ethnographic study of players' emotional practices in video games, including participant observation in online games, qualitative interviews, an analysis of YouTube videos and gaming magazines since the 1980s, this Element provides new insights into the complexity and diversity of player experiences and the pleasures of playful virtual violence. Instead of either defending or condemning the players, it contributes foundational, unprejudiced knowledge for a societal and academic debate on a critical aspect of video gaming. This title is also available as Open Access on Cambridge Core.--